2020
DOI: 10.1101/2020.01.06.896530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulation of the Gαq /Phospholipase Cβ1 Signaling Pathway Returns Differentiated PC12 Cells to a Stem-like State

Abstract: Phospholipase Cβ1 is activated by Gαq to generate calcium signals in response to hormones and neurotransmitters, and is found at high levels in mammalian neuronal tissue. Besides carrying out this key plasma membrane function, PLCβ1 has a cytosolic population that helps, in part, to drive the differentiation of PC12 cells by inhibiting a nuclease that promotes RNA-induced silencing (C3PO). Here, we show that down-regulating PLCβ1 or reducing its cytosolic population by activating Gαq to drive it to the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Phase modulation FLIM measurements were performed on the dual-channel confocal fast FLIM (Alba version 5, ISS Inc.) using a two-photon titaniumsapphire laser and a Nikon Eclipse Ti-U inverted microscope as described (15). The lifetime of the laser was calibrated each time before experiments by measuring the lifetime of Atto 425 in water with a lifetime of 3.61 ns at 80 MHz.…”
Section: Fluorescence Lifetime Imaging Measurements (Flim)mentioning
confidence: 99%
See 1 more Smart Citation
“…Phase modulation FLIM measurements were performed on the dual-channel confocal fast FLIM (Alba version 5, ISS Inc.) using a two-photon titaniumsapphire laser and a Nikon Eclipse Ti-U inverted microscope as described (15). The lifetime of the laser was calibrated each time before experiments by measuring the lifetime of Atto 425 in water with a lifetime of 3.61 ns at 80 MHz.…”
Section: Fluorescence Lifetime Imaging Measurements (Flim)mentioning
confidence: 99%
“…This binding activates Gαq, which then activates PLCβ, setting off a series of events that result in increased intracellular calcium (12). We have previously found that in model cultural neuronal cells (PC12), Gαq activation causes irreversible retraction of neurites in the first 15 minutes of stimulation (14) and causes the cells to return to a stem-like state after 72 hrs post-stimulation (15). Alternately, in C.elegans, Gαq activation transiently ruptures neuronal connections and halts locomotion which then recovers after ~30 minutes presumably due to endogenous growth factors (14).…”
Section: Introductionmentioning
confidence: 99%